Acute Coronary Artery Thrombosis Associated with Synthetic Cannabinoid Intoxication. Issue 1 (March 2015) - Dean, Stephanie A.; Jufer-Phipps, Rebecca; Fowler, David R.; Kutys, Robert; Ladich, Elena; Alexander, Russell
Synthetic cannabinoids are drugs of abuse that have rapidly gained popularity in the United States primarily due to their easy availability, inconsistent regulation, and lack of detectability on routine drug screens. Numerous case reports of adverse physical and psychological effects occurring in certain users have raised concerns that these drugs may not be as harmless as advertised, nor as similar to their plant-derived cannabis counterpart tetrahydrocannabinol (THC), as users may assume. Presented is a case of a 57-year-old man who died as a result of an acute coronary artery thrombosis immediately after smoking synthetic cannabinoids. Synthetic cannabinoids in this case were confirmed on directed postmortem toxicology testing, despite the routine postmortem drug screen being negative. Adverse cardiovascular side effects in association with these substances have only been reported in a few individuals; however, public education of the possibility for serious outcomes is needed. Medical examiners should be made aware of the potential toxicity of these drugs and the fact that they are only detected through specialized toxicological analysis. Additional research and case reports are necessary to fully understand the chemical composition and subsequent side effect profile of these drugs.